PENGEMBANGAN EMPATI MELALUI PEMBIASAAN PADA ANAK USIA DINI DI TK LAB MODEL UNIVERSITAS MUHAMMADIYAH PONTIANAK - Fitriani, Eva; Miranda, Dian; Amalia, Annisa (Universitas Tanjungpura, 2024)
This research aims to describe the implementation of empathy development through habituation in children aged 5-6 years and above, in the Muhammadiyah University Pontianak Model Laboratory Kindergarten. The research method used is descriptive qualitative. The subjects of this research were group B class teachers at the Muhammadiyah University Pontianak Model Laboratory Kindergarten. The data collection techniques used in this research are interviews, observation and documentation. The data analysis carried out was data collection, data reduction, data presentation, and drawing conclusions. The data validity checking technique is triangulation. The results of this research show that: 1) Development of empathy in the caring aspect of children aged 5-6 years through the habituation method. 2) Development of empathy aspects of tolerance in children aged 5-6 years through the habituation method. 3) Development of empathy aspects of tolerance in children aged 5-6 years through the habituation method. The conclusion in this research is a method prepared by the teacher deliberately to develop empathy through the habituation method in children aged 5-6 years. As for suggestions for developing empathy through the habituation method in children aged 5-6 years in the Model Laboratory Kindergarten, Muhammadiyah University of Pontianak, it is hoped that teachers in carrying out routine habituation must supervise and remind the child personally, get used to spontaneously conveying messages in advising using words that are easy to understand with firm, and the teacher's exemplary practice provides an example that is easy for children to imitate